2021
DOI: 10.1155/2021/2678242
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Acupuncture and Moxibustion on Chronic Prostatitis/Chronic Pelvic Pain Syndrome: A Narrative Review of Animal Studies

Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a genitourinary disease commonly seen in males, with symptoms involving pelvic pain, urinary system disease, and sexual dysfunction, which seriously affects physical and mental health, and it also influences the quality of life of patients. At present, the disease’s aetiology and pathogenesis are unclear, and there is also no effective treatment for it. Acupuncture and moxibustion have been a way to CP/CPPS, showing good curative effect with advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Moxibustion features high safety and low cost and so on including moxibustion on governor vessel acupoints, cotton moxibustion, medicinal thread moxibustion and pyretic moxibustion and the such [ 60 ]. Studies concerning moxibustion in the treatment of chronic CP/CPPS are relative less nowadays which indicated that the primary mechanism of moxibustion in the treatment of CP/CPPS is to improve whole blood reduced viscosity, white blood cell rigidity index, aggregation index and the level of fibrinogen to ameliorate hemorheology state by exerting thermal stimulation on blood vessel and tissues [ 28 , 61 ]. When moxibustion is combined with antipyretics-analgesic and anti-inflammatory drugs, anti-inflammatory and analgesic effect can be enhanced because the combination therapy can downgrade inflammatory factors, which is suggested by many studies [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moxibustion features high safety and low cost and so on including moxibustion on governor vessel acupoints, cotton moxibustion, medicinal thread moxibustion and pyretic moxibustion and the such [ 60 ]. Studies concerning moxibustion in the treatment of chronic CP/CPPS are relative less nowadays which indicated that the primary mechanism of moxibustion in the treatment of CP/CPPS is to improve whole blood reduced viscosity, white blood cell rigidity index, aggregation index and the level of fibrinogen to ameliorate hemorheology state by exerting thermal stimulation on blood vessel and tissues [ 28 , 61 ]. When moxibustion is combined with antipyretics-analgesic and anti-inflammatory drugs, anti-inflammatory and analgesic effect can be enhanced because the combination therapy can downgrade inflammatory factors, which is suggested by many studies [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) is a membrane-bound protein that induces stimuli including proinflammatory cytokines and growth factors, implying that COX-2 plays a role in both inflammation and cell growth control while being involved in neurotransmission, particularly for pain and fever. 65 In Wu et al 66 studies, they found that EA can effectively relieve pain in rats with CPPS, which may be related to the down-regulation of COX-2 and PGE2 and the up-regulation of β-EP. In addition, the above-mentioned role of the spinal cord pathway in analgesia was further confirmed.…”
Section: Potential Mechanism Of Acupuncture Treatment For Chronic Pro...mentioning
confidence: 97%
“…While the efficacy of EA on CP/CPPS has been proven in clinical practice, little is studied and elucidated, however, about the analgesic mechanism. Most animal experiments related to the mechanism of EA on CP/CPPS are without in-depth and systematic exploration of possible signal pathways and targets ( Wu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%